Saint Lucia. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Lucia during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, beekeeping, technology, costs, fodder, soil management, infrastructure and resilience against change. climate. Finally, support was given to food security, data analysis, improving infrastructure and ruminant breeding.